Homeownership for all: An American narrative - Lucy F. Ackert; Stefano Mazzotta (Journal of Risk and Financial Management, 2021)
The narrative of homeownership for all citizens is a uniquely American story. Narrative economics is a field that studies the spread of stories to explain economic fluctuations. We quantitatively examine the relationship between the American housing narrative and the run-up in home prices experienced since the Great Recession in the United States. We rely on a natural language processing (NLP) framework to measure the sentiment associated with the narrative. We then use a panel vector autoregression to empirically model the relationship between home prices and homeownership sentiment in the United States. We find that sentiment related to the American homeownership narrative is an important factor in explaining movements in home prices even after taking into account the economic factors typically thought to explain home price fluctuations. Though others have examined the role of sentiment in markets, our study is the first to empirically measure the American homeownership narrative. While this is a narrative promoted at the national level, future research might examine whether sentiment related to homeownership varies across this diverse nation.
Keywords: R28; R31; 330; home prices; homeownership; narrative economics; sentiment